Ausência do currículo da Língua brasileira de Sinais na educação básica em escolas regular de surdos e escolas inclusivas com alunos surdos no Amazonas. - Santos, Adriele Coelho dos (Brasil, 2022)
Law No. 14,191, of August 3, 2021, which amends Law No. 9,394, of December 20, 1996, on the Guidelines and Bases of National Education (LDB), which provides for the modality of bilingual education for the deaf, includes the teaching of Brazilian Sign Language (Libras) as a mandatory subject in the elementary school curriculum. In this way, it is necessary that the institutions of regular education of Deaf students, and inclusive with Deaf students, can reflect on the implementation of the teaching of Libras as a first language (L1), in the elementary school curriculum, in the aid of the educational development of the deaf students. Certainly, the essential starting point in relation to the education of the deaf is the insertion of a school curriculum from the first school years. The present course conclusion work aimed to investigate the absence of the Brazilian Sign Language curriculum in basic education in Amazonas, therefore, a qualitative, descriptive study of bibliographic and documental review was carried out.